Pemeringkatan obligasi industri perbankan di Bursa Efek Indonesia berdasarkan kinerja keuangan bank - Rohyawati Sholihin Arpadika (STIE Perbanas Surabaya, 2016)
The purpose of this study is to analyse the influence of financial performance toward bond rating of banking industry in the Indonesia Stock Exchange. The financial performance variables examined in this study include liquidity, profitability, capitalization, and asset quality. The Sample was selected using purposive sampling method. Populations of this research were taken from the banks, listed in Indonesia Stock Exchange in 2011-2015. The total population was 42 banks and only 10 of them meet the criteria. The data were analyzed using multiple regression analysis to test the hypothesis. The results of the research show that profitability has a positive influence to the bond rating, while liquidity, capitalization, and asset quality has a negative influence to the bond rating. This study imply that banks need to improve their profitabilities while maintaining their liquity risk, capital level and asset quality in order to enhance their bond ratings.